Isolation and Characterization of New Flavonoids from Fumaria Parviflora Cultivated in Iraq - Enas Jawad Kadheem (Journal of Global Pharma Technology, 2016)
Objective: The aim of this study was to investigate chemical constituents of aerial parts of Fumaria parviflora since no phytochemical investigation had been done previously in Iraq. Methods: Phytochemical screening of the extracts obtained from this plant indicated the presence of flavonoids, saponins, steroids, phenols, and alkaloids. Results: The different chromatographic and spectroscopic results revealed the presence of new flavonoids isolated from Fumaria parviflora Conclusion: The isolation and purification afforded white crystalline powder which was subjected to chemical and spectral identification by infrared and H1- C 13 nuclear magnetic resonance.